Resistance of soybean (Glycine max (L) Merrill) genotypes to soybean rust (Phakopsora pachyrhizi) in Ethiopia - Hunde, D.; Mohammed, W.; Bekeko, Z.; Abebe, A.T. (2025)
Soybean (Glycine max (L.) Merrill) is a crop of high importance in Ethiopia. However, it is threatened by Asian soybean rust (ASR) caused by the fungal pathogen Phakopsora pachyrhizi. This study aimed at screening soybean cultivars and advanced breeding lines for resistance to ASR for that will serve as sources of resistant genes for future breeding and use for production. One hundred forty-four genotypes were evaluated for resistance to soybean rust during 2021 and 2022 season at Jimma, Metu, Pawe and Jawi research centres. Plants were visually evaluated at regular intervals for days to percent severity, relative cultivar susceptibilities and sporulation levels. The results revealed that the absence of immune response at all of the locations, while 67% of the plants showed moderate susceptibility, 35% were partially resistant, 61% were susceptible and only 8% of the genotypes were highly susceptible. Only three genotypes, PI 200492, TGx-1990-57F and PI 506764, having Rpp3 and Rpp5 genes, were partially resistant to rust with RB infection type and low AUDPC value. Therefore, genotypes PI 200492, TGx-1990-57F and PI 506764 can be used as noble sources of resistance to manage soybean rust in Ethiopia and other countries harbouring similar races of the pathogen.